PENINGKATAN MINAT PEMBELAJARAN IPA DENGAN MENGGUNAKAN MEDIA TEPAT GUNA KELAS III SDN NO.15 - Sirait, Tiur Karolina; Priyadi, A Totok; AH, Maridjo (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstrak: Peningkatan Minat Pembelajaran IPA Dengan Menggunakan Media Tepat Guna Kelas 111 SDN 15 Seningkang. Tujuan dari penelitian ini adalah Ingin mendeskripsikan peningkatan perhatian, ketertarikan, kemauan dengan menggunakan Media Tepat Guna SDN 15 Seningkang. Metode yang digunakan Metode Deskriptif sedangkan bentuk penelitian yaitu Survei Kelembagaan .Minat Pembelajaran siswa yang meliputi minat perhatian pada pengamatan awal menghasilkan rata-rata 33,33%,ke siklus 111 93,75% sangat tinggi ketertarikan pada baseline rata-rata mencapai 31,25% siklus III rata-rata mencapai 91,66 % kategori sangat tinggi sedangkan kemauan baseline rata-rata mencapai 33% , siklus III rata-rata mencapai 90,62 % kategori sangat tinggi. Hal ini menunjukkan bahwapenggunaan media tepat guna dapat meningkatkan minat pembelajaran siswa kelas III Sekolah Dasar Negeri 15 Beduai, Kabupaten Sanggau. Kata Kunci: peningkatan minat belajar, media tepat guna Abstract: Increasing Interest in Natural Sciences Learning Using effective Media Class 3 Public Elementary School Subdistrict 15 Seningkang Beduai Sanggau. The purpose of this research was to describe Wish increased attention, interest, willingness learning using effective Media on science lessons on grade 3 students of SDN 15 Seningkang. The method used descriptive method of research that while the shape of Institutional Survey. Subjects were Teachers and Students Class 3 Public Primary School 15 Seningkang, amounting to 8 people. Based on the analysis of the data obtained the following results: The study was conducted as many as 3 cycles, the results obtained are a student Interests include attention to the baseline average of 33.33% lower category, I cycle an average of 53.12 % category is quite high, the second cycle an average of 75% higher and cycle III category average of 93.75% is very high category. For interest at baseline averaged 31.25% lower category, the cycle I averaged 45.83 high category, the second cycle averaged 75% higher category and third cycle an average of 91.66% category very high while the willingness to baseline average of 33% lower category, I cycle an average of 43.75% category is quite high, the second cycle an average of 75% higher and cycle III category average of 90.62 % very high category. This suggests that the use of appropriate media to enhance students' interest in learning class III elementary school 15 Beduai, Sanggau. Keywords: improving learning, effective media